Hazardous waste from the global shipbreaking industry: Historical inventory and future pathways. (September 2022) - Lin, Lin; Feng, Kuishuang; Wang, Peng; Wan, Zheng; Kong, Xianghui; Li, Jiashuo
Graphical abstract: Highlights: Historical and future waste emissions from global ship scrapping were estimated. Waste emissions from shipbreaking in South Asia increased fivefold during 1990–2019. Ship scrap is expected to grow rapidly in the future. The ratification of HongKong Convention will largely mitigate waste emissions. Abstract: Shipbreaking activities release hazardous wastes (namely, oil, asbestos, other landfillable wastes, and incinerable wastes) that harm both workers' health and the environment. However, an accurate and detailed emission inventory to support policy design of the greening reform remains lacking. By developing a framework that combines dynamic material flow model, global change assessment model and scenario analysis, this study carries out historical analysis and future projection of global ship scrap and pollutant emissions, based on ship scrap datasets. Our results show that shipbreaking sites have gradually shifted from more developed regions such as Taiwan, the European Union (EU), Japan, and Russia to the three less developed Southern Asian countries, Bangladesh, India, and Pakistan, in the past four decades. Waste emissions in these three countries have increased significantly by 6.5 times between 1990 and 2019. Although the volume of scrapped ships is expected to reach 75–95 million gross tons per year by 2050, the cumulative waste emissions from 2020 to 2050 will be reduced by 92% and 79% under the EU Convention and the Hong Kong Convention scenario, respectively. Lastly, policy implications such as how to mitigate the adverse impact of shipbreaking activities after the international conventions enter into force are comprehensively discussed.